A.D.D. : Adolescent Demo Division - Rushkoff, Douglas (DC Comics, 2011)
"The Adolescent Demo Division are the world's luckiest teen gamers. Raised from birth to test media, appear on reality TV and enjoy the fruits of corporate culture, the squad develop special abilities that make them the envy of the world, and a grave concern to their keepers"--Dust jacket.